The Needs Analysis of English Materials for Accounting Students at SMK N 1 Pematang Siantar - Pandiangan, Ferda; Dhillon, Bobby Pramjit Singh; Anggita Ristia Damanik, Bernieke (Innovative: Journal Of Social Science Research, 2025)
The aim of Vocational High Schools (SMK) is to prepare the future employees with the abilities and know-how required to be successful in their chosen industries. But SMK graduates frequently struggle to compete in the global labour market, especially when it comes to English language skills. The purpose of this study is to analyse the English language requirements of SMK N 1 Pematang Siantar accounting students. This study uses questionnaires to find out what students need, lack and wants in terms of English-language resources related to accounting. The results show that students need more specialised English language training that emphasises communication skills, accounting terminology, and the ability to understand and write financial reports. It is anticipated that this study will yield insightful information for creating English-language resources that successfully aid students' career development.